Evaluation of Routine Immunization through Supportive Supervision in Assam - Tulika Goswami Mahanta; Mridushman Saikia; Swarnali Devi Baruah (Indian Association of Preventive and Social Medicine, 2024)
Introduction: Supportive supervision is crucial for enhancing healthcare quality by improving internal relationships, resolving issues, and optimizing resources. Recent evidence from India shows it enhances immunization coverage and strengthens the local health system. Objective: To evaluate routine immunization services in terms of input and process through supportive supervision and compare service delivery between two quarters.Method: This cross-sectional study, conducted between July 2021 and February 2022, assessed the delivery of routine immunization services by frontline workers (FLWs) within Village Health Sanitation and Nutrition Day (VHSND) sessions in Assam. Five districts were selected to represent each zone of the state. Micro-plans for VHSND sessions were reviewed to visit 25-30 sessions per district based on operational feasibility. Data collected by district coordinators using a standardized checklist assessed logistics and service delivery. Statistical analysis included quarterly group comparisons using Chi-square and Fisher's exact tests (p < 0.05 significance). The findings were shared in district-level review meetings to facilitate corrective actions by all stakeholders.Results: A total of 140 VHSND sites were assessed. Paracetamol was available at 123 sites (87.9%), and updated due list was present at 120 sites (85.7%). However, Vitamin A was available at 26 sites (18.6%), ORS and Zinc were at 11 sites (7.9%) and 14 sites (10.0%), respectively. The presence of Anganwadi Workers (AWWs) at VHSND sites increased significantly from 61.2% in the first quarter to 76.7% in the second quarter (p = 0.04). Adherence to micro plans among Accredited Social Health Activists (ASHAs) was high, rising from 97.0% in the first quarter to 100% in the second quarter. Record-keeping also improved, with headcount survey documentation increasing from 83.6% in the first quarter to 95.9% in the second quarter (p = 0.01). Conclusion: The study highlighted improvements in logistics, documentation, and ASHA performance under supportive supervision. Continued focus on essential supplies and educational materials, alongside effective supervision and further research, is crucial for enhancing child health outcomes.